Analysis of the impacts of safeguard actions: Evidence from Turkey - Volkan Sezgi (Central Bank Review (CBR), 2022)
This article analyses Turkey's safeguard (SG) actions using a renovated approach to the measurement of the impacts of the SG duties with empirical application introduced by Bown and McCulloch (2004). We examine the trade impacts of 16 safeguard duties, covering 52 different 4 and 6-digit Harmonized System (HS) product categories, implemented by Turkey between 2003 and 2013, and we aim to reveal whether these measures had discriminatory impacts on those trading partners, whose imports represented a threat to the domestic importing industry. Since Turkish applications of SGs vary widely in terms of their duration, target markets and forms, this makes Turkey an interesting case study for 2003-2013 period, as Turkey mostly used SG applications based on additional financial obligations, not in the form of quotas after 2014. The empirical methodology is based on the approach introduced by Bown and McCulloch (2004), which serves as an attempt to approximate dynamic specifications in the context of cross-sectional data. Our findings show that the SGs applied by Turkey during the period of 2003-2013 effectively had a discriminatory impact on imports from major trading partners, and quotas and tariff rate quotas were more effective than tariffs for restricting imports.
Keywords: F10; F13; F14; F19; 330; Safeguard duties; Empirical studies of trade; Imports; ExportsTurkey